Determinan Tingkat Kemiskinan Di Pulau Madura - Sari, Rosalia Lukita; Khoirudin, Rifki (Jurnal Manajemen, 2019)
ABSTRACTAlthough the poverty rate in Indonesia for several years has always decreased, but for provinces or districts that have underdevelopend or lagging regions indicate that the poverty rate in the area is still quite high, especially on Madura Island. Madura Island has a high poverty rate even int the Sampang district has the highest percentage on the island of Java. With abundant natural resources which are expected to increase economic growth and reduce poverty if managed properly. This study aims to determine whether the four independent variables influence the poverty rate on Madura Island in 2004-2015. The data used in this study is to use secondary data in the form of time series data in 2004-2015 and a cross section of 4 district in Madura Island. In this research the independent variables is open unemployment, human development index, gross regional domestik product, and minimum wages. While dependent variable is poverty level in Madura Island. With using panel data estimation models and fixed effect model approaches. Based on the results of the analysis it can be concluded that partially the open unemployment rate variables have a positive and significat effect on poverty level, human development index has a negative and significant effect on poverty, gross regional products have a negative and not significant effect on poverty level, minimum wages has a negative and significant effect simultaneous poverty level all independent variables have a significant effect on poverty level in Madura Island.Keywords: Poverty, Open Unemployment, HDI, GDRP, Minimum Wage